Design and development of solar power harvester with single axis tracking mechanism - Chua Y.L.; Tay T.T.; Mathiyalagan K.A.L. (American Scientific Publishers, 2023)
Solar energy is a energy that is renewable and available all year round at different weather conditions. However, it is impossible to harvest the solar energy to the maximum capacity if the solar panel is installed fix to a certain angle. In this research, design and build of a solar panel equipped with single axis solar tracking mechanism that will rotate the panel according to the movement of the sun in the sky was carried out so that more solar rays can be absorbed and more electrical energy be harvested from the solar panels. Data were collected for various weather conditions. The performance of the solar panel equipped with solar tracker were studied and compared with stationary solar panel. With the solar tracking mechanism, the efficiency of the solar panel was increased up to 45%. 2017 American Scientific Publishers All rights reserved.